Transverse-momentum resummation for the signal-background interference in the H →γγ channel at the LHC - Cieri, Leandro Javier (2017)
We present an upgraded calculation of the effects of resonance-continuum interference for the Higgs boson decaying to two photons at the Large Hadron Collider, at next-to-leading order in the strong coupling αS, O(αS3), and including transverse-momentum (qT) resummation at next-to-leading logarithmic accuracy. We study the importance of the interference contribution in different transverse-momentum regions, with a particular focus on the low-qT region qT2 Q2 (with Q2 being the invariant diphoton mass) where resummation becomes essential for a reliable calculation.